Biotransformation of d-xylose to d-xylonate coupled to medium-chain-length polyhydroxyalkanoate production in cellobiose-grown Pseudomonas putida EM42 - Dvořák, Pavel; Kováč, Jozef; de Lorenzo, Víctor (Microbial biotechnology, 2020)
Co-production of two or more desirable compounds from low-cost substrates by a single microbial catalyst could greatly improve the economic competitiveness of many biotechnological processes. However, reports demonstrating the adoption of such co-production strategy are still scarce. In this study, the ability of genome-edited strain Pseudomonas putida EM42 to simultaneously valorize d-xylose and d-cellobiose - two important lignocellulosic carbohydrates - by converting them into the platform chemical d-xylonate and medium-chain-length polyhydroxyalkanoates, respectively, was investigated. Biotransformation experiments performed with P. putida resting cells showed that promiscuous periplasmic glucose oxidation route can efficiently generate extracellular xylonate with a high yield. Xylose oxidation was subsequently coupled to the growth of P. putida with cytoplasmic β-glucosidase BglC from Thermobifida fusca on d-cellobiose. This disaccharide turned out to be a better co-substrate for xylose-to-xylonate biotransformation than monomeric glucose. This was because unlike glucose, cellobiose did not block oxidation of the pentose by periplasmic glucose dehydrogenase Gcd, but, similarly to glucose, it was a suitable substrate for polyhydroxyalkanoate formation in P. putida. Co-production of extracellular xylose-born xylonate and intracellular cellobiose-born medium-chain-length polyhydroxyalkanoates was established in proof-of-concept experiments with P. putida grown on the disaccharide. This study highlights the potential of P. putida EM42 as a microbial platform for the production of xylonate, identifies cellobiose as a new substrate for mcl-PHA production, and proposes a fresh strategy for the simultaneous valorization of xylose and cellobiose.
Keywords: biotransformace; Biotransformation; Xylose; xylosa; celobiosa; polyhydroxyalkanoáty; Pseudomonas putida; Cellobiose; Polyhydroxyalkanoates